From large rivers to the rock record: channel patterns, bedforms and a facies model for the Amazon River - Galeazzi, Cristiano Padalino (2020)
Assumed gaps in fluvial sedimentology include large rivers, channel pattern classification and their interpretation in the rock record. Despite large rivers significance being acknowledged for decades, with a growing interest in more recent times, these fluvial systems have been relatively put aside in sedimentological research. Rivers in general have been subject of research for more than a century but the link between proposed classifications and the rock record has been problematic, with a persistent lack of effective criteria to distinguish among channel patterns in fossil fluvial systems. Channel patterns have been related to water and sediment discharge, slope, grain size, width-to-depth ratio and types of climate. Therefore, recognition of both large rivers and channel patterns in the rock record is of great significance for regional paleogeographic and paleoclimatic reconstructions, reservoir modelling, estimation of sediment input in a sedimentary basin and river management. The present work aims to cover the above-mentioned gaps concerning fluvial sedimentology by presenting three manuscripts. Manuscript (1) intends to contribute to channel pattern classification and channel pattern recognition in fluvial deposits by presenting a broad survey of alluvial rivers at a global scale to quantify channel pattern natural variability and by identifying relevant parameters for recognition in the rock record. A channel pattern classification based on quantification of sinuosity and number of channels is presented, along with a method to recognize channel patterns in the rock record based on the quantification of the variability of directions observed in the preserved bedforms in floodplains at the channel belt scale. Manuscript (2) intends to contribute to the recognition of large rivers in the rock record by discussing the relationship of channel scale and water depth with bedform morphology. The work presents high-resolution bathymetric maps of the Solimões-Amazonas River, the quantification of dune data from their riverbeds and riverbed samples. Dune morphology, height and leeside angles, as well as grain size, are related to water depth and these relationships are used to make inferences about how to identify large river in the rock record and are compared with interpreted large river fluvial deposits. Manuscript (3) intends to contribute to the recognition of large rivers in the rock record by presenting the facies models for the Solimões-Amazonas River based on the integration of morphodynamics, geophysical data and samples from the riverbed and bar tops.